Improving The Practice Of Teacher Learning Reflection Through Digital Technology-Based Lesson Study - Iman Subasman (STAI Hubbulwathan Duri, 2024)
This research explores the development of a lesson study model integrated with digital strategies, aiming to enhance collaborative learning among teachers. Using qualitative methodology, the study involved teachers from different disciplines in secondary schools. Data collection included surveys, interviews, and analyses of teaching practices. The main focus was on implementing digital tools such as online learning platforms, discussion forums, and collaborative learning among teachers. Data analysis uses Interpretive Phenomenological Analysis (IPA), which aims to determine the phenomenon that is the focus of the research. The results showed significant improvements in engagement, reflection, and exchange of teaching practices. Further analysis revealed that integrating digital technologies enriched the lesson study experience by providing wider access to resources and learning communities while facilitating more efficient data collection and analysis. However, challenges related to technology training and the integration of digital resources in the curriculum were also identified. This research provides new insights into the potential of digital technology in enhancing lesson study and suggests the need for a structured approach to technology integration in teacher professional development. The findings have the potential to make significant contributions to teacher professional development literature and educational practice, particularly in adapting digital technologies for effective collaborative learning.